Filogeografia de Terpides sooretamae Boldrini & Salles (Ephemeroptera: Leptophlebiidae) - Rizzi, Evandro Apolinario (2016)
Terpides sooretamae Boldrini & Salles 2009 occurs in various Brazilian biomes, at watercourses ecologically and physically diversified from Atlantic rainforest and Cerrado (Brazilian savannah). The bibliography exhibits many cases in which species that occur at different places, located at distinct biomes, show large variability at molecular level. The aim of this work was to investigate the populational structure of Te. sooretamae and its dispersion powerful in a geographically diverse, remarkable ecologically and unknown molecularly system: the genetic patterns of structuration of such populations at whole distributional range. For this purpose, it was utilized an amount of 155 individuals. For the DNA extraction, it was applied a Promega® protocol of DNA extraction; two regions of mtDNA were amplified (COI and COII), purified and sequenced. The sequences (57 of COI and 80 of COII) were conferred with BLAST (similarities search tool), after those was aligned and edited. Some analysis were conducted, such as phylogenetic analysis of maximum-likelihood, calculations of haplotypic diversity and generation of haplotype networks, AMOVA, neutrality tests and mismatch distributions. The results show a strong affinity between individuals from Southeast Brazil and Northeast Brazil, with low values of genetic variation between its sequences; based on this, we can say that the populations from Southeast Brazil and Northeast Brazil keep birectional gene flow. The Fu’s Fs and Tajima’s D values plus the mismatch distribution graphics suggest that both populations are through in a recent demographic expansion. The populations from Mato Grosso and Mato Grosso do Sul, on the other hand, show high divergence compared to the Southeast and Northeast populations, where the ones from Mato Grosso do Sul show extremely high values. With high molecular variation compared to other populations and showing a peculiar position in the maximum-likelihood, the populations from Mato Grosso do Sul may constitute a distinct species.